Autism Attenuates Sex Differences in Brain Structure: A Combined Voxel-Based Morphometry and Diffusion Tensor Imaging Study - Beacher, F.D.; Minati, L.; Baron-Cohen, S.; Lombardo, M.V.; Lai, M.-C.; Gray, M.A.; Harrison, N.A.; Critchley, H.D. (American Journal of Neuroradiology, 2012)
BACKGROUND AND PURPOSE: It has been proposed that autism spectrums condition may represent a form of extreme male brain (EMB), a notion supported by psychometric, behavioral, and endocrine evidence. Yet, limited data are presently available evaluating this hypothesis in terms of neuroanatomy. Here, we investigated sex-related anatomic features in adults with AS, a “pure” form of autism not involving major developmental delay. MATERIALS AND METHODS: Males and females with AS and healthy controls (n = 28 and 30, respectively) were recruited. Structural MR imaging was performed to measure overall gray and white matter volume and to assess regional effects by means of VBM. DTI was used to investigate the integrity of the main white matter tracts. RESULTS: Significant interactions were found between sex and diagnosis in total white matter volume, regional gray matter volume in the right parietal operculum, and fractional anisotropy (FA) in the body of the CC, cingulum, and CR. Post hoc comparisons indicated that the typical sexual dimorphism found in controls, whereby males have larger FA and total white matter volume, was absent or attenuated in participants with AS. CONCLUSIONS: Our results point to a fundamental role of the factors that underlie sex-specific brain differentiation in the etiology of autism. ANCOVAanalysis of covarianceAQautism quotientASAsperger syndromeASCautism spectrum conditionsCCcorpus callosumCRcorona radiataCSTcorticospinal tractEMBextreme male brainFAfractional anisotropykecluster extent in isotropic 2 × 2 × 2 mm MNI space voxelsMCPmiddle cerebellar peduncleMDmean diffusivityMNIMontreal Neurological InstituteNARTNational Adult Reading Testηp2effect size expressed as partial-eta squaredSLFsuperior longitudinal fasciculusVBMvoxel-based morphometry